2011
DOI: 10.1007/s10811-011-9668-1
|View full text |Cite
|
Sign up to set email alerts
|

Value-added fermentation of Ecklonia cava processing by-product and its antioxidant effect

Abstract: The interest in the extraction of polyphenolic compounds from plant materials is focused on upgrading of the large amount of by-products coming from food or cosmetics industries from which the press residues have particularly high contents of phenolics. In this study, for value-added use of the brown seaweed Ecklonia cava processing by-product (ECPB), which can be obtained after polyphenolic extraction of E. cava, it was fermented by the yeast Candida utilis and its antioxidant activities were evaluated by 1,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In another study, an antioxidant phloroglucinol was isolated and the isolated compound found to possess similar antioxidant activity with L-ascorbic acid (Lee et al 1996). One of our previous works demonstrated the antioxidant effect of fermented E. cava processing by-product (Wijesinghe et al 2011). Further we reported that, the antioxidant activity of E. cava processing by-product mainly due to the phlorotannins in the extract.…”
Section: Biological Activities Of Brown Seaweeds With Special Focusesmentioning
confidence: 93%
“…In another study, an antioxidant phloroglucinol was isolated and the isolated compound found to possess similar antioxidant activity with L-ascorbic acid (Lee et al 1996). One of our previous works demonstrated the antioxidant effect of fermented E. cava processing by-product (Wijesinghe et al 2011). Further we reported that, the antioxidant activity of E. cava processing by-product mainly due to the phlorotannins in the extract.…”
Section: Biological Activities Of Brown Seaweeds With Special Focusesmentioning
confidence: 93%
“…Wijesinghe et al [85] confirmed the presence of PHT triphloroethol-A, eckol, dieckol, and eckstolonol in investigated Ecklonia calva samples, while Machu et al [62] confirmed the presence of gallic acid ( E. bicyclis, H. fusiformis ), 4-hydroxybenzoic acid ( U. pinnatifida ), epicatechin ( E. bicyclis , Sargassum fusiforme, Saccharina japonica ), catechin gallate ( E. bicyclis, S. japonica ) and epigallocatechin ( S. japonica ).…”
Section: Brown Algae Phenolicsmentioning
confidence: 99%
“…The cells were maintained at 37°C in humidified atmosphere of 5% CO 2 E. cava processing by-product (EPB) has both antioxidant and anti-inflammation effects and rich in polyphenols (Wijesinghe et al 2012(Wijesinghe et al , 2013. However, the anti-inflammatory effects of EPB have not yet been assessed.…”
Section: Cell Culturementioning
confidence: 99%